Effects of UV and white light illuminations on photosensing properties of the 6,13-bis(triisopropylsilylethynyl)pentacene thin film transistor - Gunduz, Bayram; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
The effects of UV and white light illuminations on the electrical and photosensing properties of the 6,13-bis(triisopropylsilylethynyl)pentacene thin film transistor were investigated. The photosensitivity (I-ph/I-dark) values of the transistor in the OFF state were found to be 1.156 and 2.12 under UV 365 nm (for V-g = -10V) and white light illuminations (for V-g = -10V and P = 100 mW/cm(2)), respectively. The threshold voltage value of the TIPS-pentacene transistor was shifted from a smaller (0.215V) value to higher (1.095V) value with UV illumination, while it was shifted from a negative value (-1.29 V) to positive value (0.525V) with white light illumination. The mobility mu value (3.412 x 10(-2) cm(2)/Vs) of the TIPS-pentacene transistor under dark is lower than that of the values under UV and white light illuminations. The sub-threshold swing value under dark is higher than that of under UV and white light illuminations. The interface trap density of the TIPS-pentacene transistor is decreased with increasing illumination. The lowest D-it value (0.941 x 10(13) eV(-1) cm(-2)) of the TIPS-pentacene transistor causes the highest mobility (6.322 x 10(-2) cm(2)/Vs). The photoresponsivity R values of the TIPS-pentacene transistor vary from 11.58 mA/W to 53.48 mA/W. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TIPS-pentacene transistor; Photoresponsivity; UV and white light illuminations